The comparison and analysis the ground penetrating radar GPR equipments on electromagnetic radiation data / Akid Rais Noorizan - Noorizan, Akid Rais (2019)
The Ground Penetration Radar (GPR) becomes a popular device in investigation of the underground utilities in recent years. GPR use of electromagnetic radiation to detect and record the properties of underground utility. Besides that, GPR can analyse the type and position of utility objects. However, the performance accuracy of GPR models is an important issue that should be considered. This research conducts between two models of MALA ProEx GPR and Noggin Smart Cart 250MHz GPR by focusing on the basic principle of GPR, accuracy analysis and calibration method implemented on GPR. The survey work has been performed to identity the capabilities of GPR equipments with same frequency which is 250MHz to detect underground utility objects at Gurun, Kedah which required steps of study area preparation, data collection, data processing and interpret the results of data. In this study area were buried the utility objects of PVC pipe and Metal pipe and their original depth were 2.25 metres and 2.10 metres respectively. These surveys were organised on a grid pattern across the surface of land in the test facility. In addition, data analysis was carried out to compare between two models of GPR equipments. This research provide proper guideline and assists surveyors to select the suitable equipments regarding on application especially on utility mapping in terms of accuracy.